Mindful Moms: Motivation to Self-Manage Depression Symptoms. Issue 4 (July 2020) - Russell, Sasha; Aubry, Christine; Rider, Amy; Mazzeo, Suzanne E.; Kinser, Patricia A.
Abstract: Background: Nearly 20% of women in the United States experience depressive symptoms during the perinatal period, with known detrimental effects for the mother, child, and family. Depressive symptoms affect motivation to engage in healthy behaviors and self-management of symptoms. Purpose: The purpose of this study was to explore the experiences of women with depressive symptoms who participated in a 12-week mindful physical activity intervention (Mindful Moms) throughout their pregnancy. Study Design: In this qualitative study, we explore the lived experience of women with depressive symptoms who participated in Mindful Moms, a self-management intervention involving nurse-led motivational sessions and group-based mindful physical activity (yoga). Methods: Semistructured interviews conducted at approximately 6 weeks postpartum provided rich qualitative data that was analyzed using a phenomenological approach. Results: Twenty-five women participated. Findings suggest that participants in Mindful Moms felt empowered to manage their depressive symptoms through the combination of four key factors: a newly recognized need for help, a felt sense of physical and emotional benefit from participation, the power of shared safe space with other pregnant women, support from study staff, and an overall sense of empowerment. Clinical Implications: Mindful Moms appears to be a feasible and acceptable approach to enhancing motivation to self-manage depressive symptoms in pregnant women. Nurses working with childbearing women should be aware of the potential benefits of self-management strategies, such as mindful physical activity and motivational interviewing, for women facing perinatal depressive symptoms. Abstract : Mindful Moms is a self-management intervention involving nurse-led motivational interviewing and group-based mindful yoga. Women who participated in the program shared their experiences. Based on findings, Mindful Mom appears to be a feasible and acceptable approach to enhancing motivation to self-manage depressive symptoms in pregnant women.